PERLINDUNGANSAKSI PELAPOR DALAM PERKARA PENYALAHGUNAAN NARKOTIKA PADA TINGKAT PENYIDIKAN (Studi Pada Satuan Reserse Narkoba Kepolisian Resor Kota Padang) - Amris, Anton (Universitas Ekasakti, 2019)
The protection of the reporter as a witness who is willing to provide information for the purpose of disclosing criminal acts of drug abuse is regulated in Article 5 of Law Number 31 Year 2014 concerning Protection of Witnesses and Victims and Article 100 of Law Number 35 Year 2009 concerning Narcotics. The need for reporters to be given protection is very important to increase the participation of the community in helping law enforcement officers prevent and eradicate and disclose the proliferation of narcotics circulation. But in practice there are still many witnesses who do not want to provide information due to the lack of adequate guarantees for the protection provided by law enforcement officials.